Factors influencing seniors' willingness to pay intention for exercise in the civil sports and recreation centers - Fang, Chin-Yi; Chen, Po-Yu; Liao, Yung (Frontiers in Public Health, 2023)
Background: The increasing trend for an older population is a phenomenon that is well recognized around the world. The percentage of senior citizens participating in sports, recreation and leisure activities is also increasing in order to sustain a healthier society. As long as seniors recognize the importance and benefits of keeping healthy, they would prefer to be active in various sports and fitness activities. The seniors could engage in making decisions about their own health by exercising regularly and by encouraging their similar-age peers. The civil sports & recreation centers (CSRC) in Taiwan have adopted operating-transfer (OT) and are located mainly in metropolitan areas, with programs consisting of indoor sports offering people daily exercise. The major aims of the CSRC are to keep the citizens’ good health and not to be the city government’s financial burden. The extant literature examines determinants of general consumer behavior, neglecting studies on older adults. This study aims to explore the factors influencing seniors’ willingness to pay (WTP) more for exercise in CSRCs outside of free hours. Methods: This mixed-method study consists of quantitative and qualitative analyses. For the quantitative component, we invited five experts in the sport industry from the industry and academia to evaluate the validity of the questionnaire. A questionnaire consisting of motivation, exercise involvement and constraint constructs in the quantitative method was administered to 193 older adults in CSRCs. The collected data was analyzed through descriptive statistics, t-test, one-way analysis of variance (ANOVA) and structural equation model (SEM). Results: Empirical results indicate that WTP in groups of people aged 75–79, 70–74 and 65–69 is higher than in the group of people aged 85 and above. Exercise involvement and motivation had more of a positive impact on seniors’ WTP. Conclusion: This study contributes to explore the determinants of seniors’ WTP intention. Motivation and exercise involvement had significantly positive impact on seniors’ WTP intention.